Peranan Komite Madrasah dalam Peningkatan Mutu Pendidikan di Madrasah Ibtidaiyah Negeri Lopian Kecamatan Badiri - Tanjung, Rahmadi; Erawadi; Hasibuan, Zainal Efendi (AL-IBROH: Jurnal Ilmu Pendidikan dan Keguruan, 2024)
Education is a shared responsibility, not only of the government but also of parents, the community, and the madrasah committee. Effective collaboration is essential to creating a conducive and enjoyable learning environment. This study employs a qualitative method to examine the quality of education at MIN Lopian, the role of the madrasah committee in improving educational quality, and the supporting and inhibiting factors. The research informants include the madrasah committee, homeroom teachers, and the vice principal for curriculum affairs. Data were collected through observation, interviews, and documentation. The findings reveal that the madrasah committee plays a role as an advisor in program planning, a financial and manpower supporter, a supervisor of educational policies, and a mediator between parents and the madrasah. The quality of education at MIN Lopian is supported by students' motivation, teacher guidance, and adequate facilities. The teaching and learning process incorporates various methods, including daily religious practice. As a result, students excel academically and non-academically while demonstrating discipline and good character. The factors supporting the committee’s role include a shared vision, effective communication, and transparency between the madrasah and the committee. Meanwhile, the main challenges are limited human resources, time constraints, and coordination issues among committee members.